ANALYSIS OF ENTREPRENEURSHIP LEARNING IN FOSTERING THE SPIRIT OF BUSINESS OF STUDENTS IN ISLAMIC BOARDING SCHOOLS: A SYSTEMATIC LITERATURE REVIEW (SLR) - Pangesti, Sri Yuliani; Fuad, Ainun; Wardana, Ludi Vishnu; Wati, Andy Prasetyo (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This research explores the role of entrepreneurial learning in increasing entrepreneurial interest in Islamic boarding schools. In the context of economic and social challenges, entrepreneurship among students can be a sustainable solution. The Systematic Literature Review method is used to analyze previous research. The results show that entrepreneurial learning has a positive impact, with factors such as learning methods, motivation, and social environment playing an important role. The implications are for the development of more targeted and effective learning programs in Islamic boarding schools, which can increase the skills and entrepreneurial interests of students and have a positive impact on the economic and social development of the pesantren community